Regulation of Leukocytes by TspanC8 Tetraspanins and the “Molecular Scissor” ADAM10 - Matthews, Alexandra L.; Koo, Chek Ziu; Szyroka, Justyna; Harrison, Neale; Kanhere, Aditi; Tomlinson, Michael G. (Frontiers in Immunology, 2018)
A disintegrin and metalloproteinase 10 (ADAM10) is a ubiquitously-expressed transmembrane protein that functions as a ‘molecular scissor’ to cleave the extracellular regions from its transmembrane target proteins. ADAM10 is well-characterized as the ligand-dependent activator of Notch proteins, which control cell fate decisions. Indeed, conditional knockouts of ADAM10 in mice reveal impaired B-, T- and myeloid cell development and/or function. ADAM10 cleaves many other leukocyte-expressed substrates. On B-cells, ADAM10 cleavage of the low affinity IgE receptor CD23 promotes allergy and asthma, cleavage of ICOS ligand impairs antibody responses, and cleavage of the BAFF-APRIL receptor TACI, and BAFF receptor BAFFR, reduce B-cell survival. On microglia, increased ADAM10 cleavage of a rare variant of the scavenger receptor TREM2 may increase susceptibility to Alzheimer’s disease. We and others recently showed that ADAM10 interacts with one of six different regulatory tetraspanin membrane proteins, which we termed the TspanC8 subgroup, comprising Tspan5, Tspan10, Tspan14, Tspan15, Tspan17 and Tspan33. The TspanC8s are required for ADAM10 exit from the endoplasmic reticulum, and emerging evidence suggests that they dictate ADAM10 subcellular localization and substrate specificity. Therefore, we propose that ADAM10 should not be regarded as a single scissor, but as six different scissors with distinct substrate specificities, depending on the associated TspanC8. In this review, we collate recently-published transcriptomic data to present the TspanC8 repertoires of leukocytes, and we discuss the potential role of the six TspanC8/ADAM10 scissors in leukocyte development and function.